1985
DOI: 10.1042/bj2300019
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bile-acid synthesis. Role of sterol carrier protein2 in the biosynthesis of 7α-hydroxycholesterol

Abstract: Sterol carrier protein2 (SCP2) is known to stimulate utilization of cholesterol in enzymic reactions in which cholesterol is the substrate. Substantial recent experimental evidence indicates that SCP2: activates enzymic conversion of intermediates between lanosterol and cholesterol; stimulates the microsomal conversion of cholesterol into cholesterol ester in rat liver; and enhances mitochondrial utilization of cholesterol for pregnenolone formation in the adrenals. The conversion of cholesterol into 7 alpha-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Animal experiments confirm that SCP2 plays an essential role in the transportation of newly synthesized cholesterol into bile, and that SCP2 can rapidly transfer cholesterol from the endoplasmic reticulum directly into the bile without the involvement of the cellular microtubule system and the Golgi (22). Fuchs et al (14,23) observed the phenomenon in the stone-susceptible mice, and noted that the SCP2 protein and mRNA levels rose at the same time and concluded that the transcriptional upregulation of SCP2 led to the higher levels of SCP2 in hepatocytes, thus increasing bile cholesterol and promoting gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments confirm that SCP2 plays an essential role in the transportation of newly synthesized cholesterol into bile, and that SCP2 can rapidly transfer cholesterol from the endoplasmic reticulum directly into the bile without the involvement of the cellular microtubule system and the Golgi (22). Fuchs et al (14,23) observed the phenomenon in the stone-susceptible mice, and noted that the SCP2 protein and mRNA levels rose at the same time and concluded that the transcriptional upregulation of SCP2 led to the higher levels of SCP2 in hepatocytes, thus increasing bile cholesterol and promoting gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In its role as a transporter, this protein participates in the transportation of cholesterol inside the cell and through the cytoplasm membrane, (8,9) as well as in the rapid transportation of newly synthesized cholesterol from the endoplasmic reticulum into bile without the intervention of the cytomicrotubule system and Golgi bodies (10). Additionally, some researchers indicate that it may have a role in the biosynthesis of cholesterol, (11)(12)(13) and in the transformation of cholesterol to bile acids (14,15), cholesterol esters (16) and sterols (17). Our former findings indicated that SCP2 was overexpressed in patients with hereditary cholesterol gallstones when compared to patients with non-hereditary cholesterol gallstones, and that SCP2 may be a potential genetic factor that contributes to the formation of cholesterol gallstones (18).…”
Section: Introductionmentioning
confidence: 99%
“…NsL-TP stimulates, in vitro Van Amerongen et al, 1989), phospholipids (Crain & Zilversmit, 1980; Nichols, 1988; Van Amerongen et al, 1989), sphingomyelin (Crain & Zilversmit, 1980), gangliosides (Bloj & Zilversmit, 1981), and neutral glycosphingolipids (Bloj & Zilversmit, 1981). As a consequence of nsL-TP-mediated transfer of cholesterol, nsL-TP was shown to stimulate microsomal conversion of (Seltman et al, 1985;Lidstrom-Olssen & Wikvall, 1986), and steroid hormone synthesis (Chanderbhan et al, 1982; Vahouny et al, 1983; Van Noort et al, 1986, 1988a. Although many studies have focused on the role of nsL-TP in lipid metabolism, the exact mechanism by which nsL-TP mediates the transfer of cholesterol and of phospholipids is not yet fully understood.…”
mentioning
confidence: 99%
“…1). This protein, identical to sterol carrier protein 2 (SCP2), stimulates the enzymatic conversion of lanosterol to cholesterol during the biosynthesis of cholesterol and enhances the synthesis of bile acids (2,3). It has recently been shown that nsLTP, first thought to be a cytosolic protein (4), is localized mostly in peroxisomes, where it is concentrated in the matrix (5-7), in both rat liver and adrenal gland.…”
mentioning
confidence: 99%